PROVIDENSIA ALLAH TERHADAP PENYEMBAHAN BERHALA BANGSA ISRAEL PADA MASA HAKIM-HAKIM (HAK 2:6-23) - Amanda Shalomita Christnanda (Inculco Journal of Christian Education, 2021)
AbstractThe providance of God is a reformed theological concept of God's care for His creation and everything that happens in God's sovereignty. Crime events are also God's decree, but humans must be responsible for the choices they make. Seen from the background of the events that occurred to the nation of Israel at the time of the Judges, idolatry carried out by the Israelites was a decree from God that aimed to bring the Israelites to God's plan. This article aims to reveal the relationship between God's providence and the idolatry of the Israelites in the time of the Judges. Abstrak : Providensia Allah merupakan konsep teologi reformed tentang pemeliharaan Tuhan atas ciptaan-Nya dan segala sesuatu yang terjadi ada dalam kedaulatan Allah. Peristiwa kejahatan juga merupakan ketetapan Allah, namun manusia harus bertanggung jawab atas pilihan yang diambilnya. Ditinjau dari latar belakang peristiwa yang terjadi kepada bangsa Israel pada masa Hakim-hakim, penyembahan berhala yang dilakukan bangsa Israel merupakan ketetapan dari Allah yang bertujuan untuk membawa bangsa Israel kepada rencana Allah. Artikel ini bertujuan untuk mengungkapkan hubungan antara providensia Allah dengan penyembahan berhala bangsa Israel pada masa Hakim-hakim.